Prevalence and predictors of cardiovascular disease risk among people living with human immunodeficiency virus in Nigeria - Abiodun Isah; Olujuwon Ibiloye; Temiwoluwa Omole; Oluwatobi Olaniyi; Plang Jwanle; Ifeyinwa Onwuatelo; Jay Osi Samuels; Prosper Okonkwo (AIDS Research and Therapy)
Abstract Introduction Advances in HIV/AIDS treatment have transformed HIV into a manageable chronic condition. However, cardiovascular disease (CVD) and other non-communicable diseases are increasingly emerging among people living with HIV (PLHIV), especially in developing countries. This study assessed the prevalence and determinants of CVD risk among PLHIV in Nigeria. Methods A cross-sectional study was conducted from February to May 2024 across ten Nigerian health facilities, involving 1,000 PLHIV on antiretroviral therapy (ART). Data on socio-demographic characteristics, lifestyle behaviors, family history of CVD, and HIV-related clinical factors were collected through structured questionnaires and medical records. Chi-square tests and logistic regression analyses were conducted using SPSS v24, with significance set at p < 0.05. Results Participants had a median age of 48 years (IQR: 41–56), and 60.7% were female. Hypertension (26.2%), overweight (27.9%), high-risk waist-hip ratio (39.6%), and obesity (19.6%) were common. Overall, 61.1% were at risk for CVD. Significant predictors of higher CVD risk included urban residence (aOR: 1.48; 95% CI: 1.13–1.94), smoking (aOR: 2.16; 95% CI: 1.26–3.68), family history of hypertension (aOR: 1.7; 95% CI: 1.2–2.4), being on ART for ≥ 10 years (aOR: 1.5; 95% CI: 1.1–2.01), and infrequent consumption of high-fat, sugar, and salt (HFSS) foods (aOR: 1.4; 95% CI: 1.1–1.9). Conversely, being retired or a student was associated with lower risk. Conclusion CVD risk is prevalent among PLHIV in Nigeria and is linked to demographic, clinical, and lifestyle factors. Targeted, integrated interventions, and client-centered care strategies are required to reduce CVD burden among PLHIV.